Credibility of e-commerce trends in the Arab environment - أبي سعيد الديوه جي (Iraqi Journal for Administrative Sciences, 2024)
The research attempts to explain the foundations on which e-commerce was based and how important scientific initiatives and databases were in establishing e-commerce globally. Therefore, such global attempts, which have strengthened the status of e-commerce and enabled its widespread spread, will be reviewed. On the other hand, the Arab environment, with its current components, has taken the initiative to deal with this electronic commerce, according to the data available in the environment, which appears to be facing obstacles and difficulties. It is assumed that it should be taken up first at certain levels, and the possibility of spreading it at the overall level whenever the variables and circumstances become available and appear appropriate otherwise. The discrepancy seems clear between one region and another in the Arab world, which did not benefit from the most important element of e-commerce: "language" in dealing and commercial Exchange. The research shows that there is an exaggeration in the use of electronic commerce, as dealing with services still comes to the fore while coping with goods has only witnessed limited areas, and that dealing at the level of organizations with each other is relied upon, and that companies suffer from scarcity or reluctance in dealing with Before individuals globally, especially for domestic goods, the research is an attempt to review these components and link them to the Arab environment, which is waiting for new initiatives to come up with a new model that is compatible with this environment. The term e-commerce has taken a prominent position, exceeding expectations. This term appeared seven years ago, and the term began to be repeated in the commercial and scientific arena day after day. Countries benefited from active participation in using the meanings of this term and its effective applications, which pushed commercial operations to high levels. Countries began By legislating laws regulating this type of trade and holding seminars, meetings and conferences. Many countries are racing to introduce and use it and invest millions to provide the infrastructure that guarantees its success. Trade is defined as "the buying and selling of goods and services of various types to achieve profits" or "the Exchange of goods and services. The parties to the commercial transaction are: Buyers, sellers and producers. E-commerce lies in buying and selling via the Internet, which means that electronic commerce is the process of offering goods and services, buying, selling, and paying through the Internet. But suppose electronic commerce is one of the inevitable issues that is supposed to take its place in the Arab environment amidst many and varied variables and contradictions. How can these contradictions be reconciled with the modern phenomenon of electronic commerce? Has the Arab environment benefited from previous experiences in this field? Is it possible for the Arab environment to be unique in having special models that do not necessarily have to be far from the current scientific reality in the world but rather have a certain specificity that stems from the available components? This is what we will try to review in this research.